Therapeutic outcomes of microwave coagulation therapy for hepatocellular carcinoma as a less invasive surgery - Midorikawa, Takemasa; Hatakeyama, Toshiyuki; Ishibashi, Kazuyoshi; Izuno, Hisanori; Saito, Mitsuo; Kikuchi, Hiroaki; Maezawa, Koji; Miyakawa, Kiyoshi; Fujiwara, Yasuro; Uemichi, Osamu (Journal of Microwave Surgery, 2003)
The liver function of the most patients with HCC was impaired, because of complicated chronic hepatitis or liver cirrhosis. We evaluated the therapeutic outcomes by comparison between MCT and hepatectomy for HCC. The subjects were 94 patients with HCC undergoing MCT (n=48) or hepatectomy (n=46) from 1997 to 2003. The hepatic functional reserve was significantly worse in the MCT group than those in the Heaptectomy group. Operative bleeding and the levels of inflammatory markers were significantly lower in the MCT group. The rate of survival was not significantly. MCT for the patients of HCC with impaired liver functions is safe, less invasive, and more reliable local treatment. We suggest that therapeutic modality should be selected carefully for the patients with HCC.